Linking methane fluxes and oxidation rates to methane oxidizing bacteria in an Arctic terrestrial methane seep, Svalbard - Nagel, Franziska (UiT Norges arktiske universitet, 2020)
Global warming has especially detrimental effects on Arctic regions. One major issue is permafrost thaw and sub-permafrost methane escape via surface seeps. While the mitigation potential of methane-consuming bacteria on marine pingo-like methane seeps is well described, terrestrial methane seeps are still understudied. Recently, open system pingos have gained attention as terrestrial methane seeps. Lagoon Pingo (N 78°14'22'', E15°45'16''), a near-shore open system pingo in the Adventdalen valley, Svalbard, was chosen as a study site to investigate the potential impact of methane-oxidizing bacteria on methane evasion from open system pingos. During a fieldwork campaign in August 2019, methane fluxes were measured across the entire site and compared to the distribution of the site’s methane oxidation potentials. The centre of evasion was found at the groundwater-discharging source. The discharged waters were carried away by an associated stream, which gradually emitted methane to a distance of up to 80 meters from the source. While waters from the site were not shown to possess the ability to oxidize methane aerobically, an abundance of methane oxidizing bacteria was found in sediments that were covered with methane emitting waters, creating the potential to oxidize methane. Furthermore, using Lagoon Pingo sediments as inoculum, enrichments have brought a methane oxidizing bacterial strain in culture. This novel Methylobacter sp. seems to produce exospores, a feature not previously described for cultured Methylobacter species. The new knowledge provided by this thesis is a fundament for evaluating the bacterial impact on methane evasion from open system pingos. This in turn could be used to improve predictions of the contribution of open system pingos to the global methane budget.